New aspects of coccidia-triggered modulation of the host cellular cell cycle - Rojas Barón, Lisbeth Cecilia; Justus Liebig University Giessen (My University, 2025)
Apicomplexan parasites are a large group of protists with an obligate intracellular lifestyle, impacting human and veterinary health worldwide. The Sarcocystidae family contains notable species like Toxoplasma gondii, a critical zoonotic pathogen, and Neospora caninum, cause of abortion in cattle and of neurological disorders in canid hosts. Although both parasites differ in their host specificity and in distinct aspects of their life cycle, they also share common characteristics in their sophisticated ability to modulate host cell functions. Here, we focused on molecular and cellular mechanisms involved in parasite infection-driven host cell cycle dysregulation. T. gondii is well recognized to significantly affect host cell cycle progression, regardless of MOI, infection times and, importantly, the cellular model used in experimentation. While many former studies used immortalized or tumour cells, potentially exhibiting dysregulated cell cycling, current analyses addressed T. gondii infections in primary cells by analyzing different cell types (fibroblasts, endothelial and epithelial cells) and donor species (human, bovine). Here, we revealed a T. gondii-driven cell type- and origin-independent S-phase arrest. Notably, cyclin B1, a critical regulator of mitosis entry, remained unchanged across all cell types, indicating that mitosis checkpoint modulation is not involved in host cellular S-phase stasis. Beyond interphase effects, T. gondii infection led to aberrant mitosis in all mitotic subphases, characterized by chromosome miscondensation and supernumerary centrosome formation. Moreover, all cell types showed an increased proportion of binucleated phenotypes, indicating impaired cytokinesis, which also occurred independently of cell origin or type. Given that different T. gondii genotypes show varying pathogenicity in the field, host cell cycle regulation may also be influenced by haplotypes. To explore this, different strain infections (Me49, NED) were comparatively analysed in primary host cells. In line with RH, Me49 and NED strains also induced host S-phase arrest. Further analyses on key regulatory proteins of S-phase control and M-phase enter revealed a cyclin B1 downregulation only for NED infections. Additionally, the mitotic rate was reduced by NED infections, concomitant with altered chromosome arrangement and irregular chromosome bridges within the mitotic spindle. Moreover, T. gondii Me49 and NED strains also led to an enhanced proportion of binucleated host cells, indicative of cytokinesis failure. Thereby, this cellular phenotype was here described for the first time for all haplotype infections, demonstrating cytokinesis impairment as intrinsic, haplotype-independent mechanism of T. gondii. Chromosome missegregation and cytokinesis impairment are key features of chromosome instability being associated with DNA damage in cells. As determined in the current work, RH, Me49 and NED strains indeed all induced DNA double-strand breaks with the RH strain driving - by far - the most pronounced effects. Moreover, referring to cytokinesis failure, a significant proportion of both RH- and NED-infected binucleated host cells showed DNA damage foci. Interestingly, NED-infected cells exhibited an increased proportion of micronuclei, thereby highlighting parasite strain-specific insults on host cellular genomic stability. Under genotoxic stress, cells activate the DNA damage response to maintain genome integrity. Repair mechanisms for this type of damage include the homologous recombination (HR) and non-homologous end joining (NHEJ) pathways, which were here profiled for RH strain infections. As expected, the HR pathway was activated by an upregulation of ATM pathway-related proteins, which classically are induced by DNA double-strand breaks. Finally, current cell cycle-related analyses were extended to N. caninum infections in the same host cell type to elucidate eventual species-specific strategies. N. caninum caused late S-phase arrest concomitant with cyclin A2 and cyclin B1 upregulation at 24 h p. i. (followed by cyclin A2 decrease at 32 h), confirming irregularities from S- to G2/M transition-phase. Interestingly, irregular nuclear morphologies were observed in N. caninum-infected cells, illustrated as invaginations and stretches of nuclear membrane disintegration and quantified as smaller nuclear areas, indicating that the host cellular nuclear structure was affected by N. caninum. Further analyses on the nuclear protein lamin B1 revealed an increased proportion of cells with inhomogeneous lamin B1 patterns, several nuclear folding and invaginations, phenomena reported for the first time for coccidian infections. Moreover, the perinuclear area was altered since actin filaments normally being anchored to the nuclear periphery and transversing the nucleus (actin cap) were absent in infected cells alongside with a decreased total cellular actin abundance, highlighting that N. caninum infection indeed interferes with the host actin cytoskeleton leading to nuclear membrane destabilization and abnormal shaping. Overall, these findings contrast with alterations induced by different T. gondii strains, emphasizing species-specific events in host cell modulation.
Keywords: Apicomplexan parasites; Toxoplasma gondii; Neospora caninum; cell cycle dysregulation; chromosome instability; DNA damage; binucleated phenotypes; primary cells; ddc:630